A first look at monthly fluctuations of Sr/Ca in Porites sp. from The East and West Coast of Peninsular Malaysia - Liyana Amir; Che Abd Rahim Mohamed (Penerbit Universiti Kebangsaan Malaysia, 2019)
Coral cores were collected from four locations around Peninsular Malaysia and Sr/Ca ratios were measured. The interannual temperature ranges from 26.8-31.5°C. The sites chosen were Pulau Redang, Port Dickson, Pulau Tioman and Pulau Payar due to the Southeast Monsoon and Northwest Monsoon influences coupled with effects of the El Niño Southern Oscillation towards the region. Coral powder samples were sampled at 1 mm intervals along apex of extending corralites visible along the coral slab surface and analysed using ICP-OES. Ordinary least squares regression analysis showed that Sr/Ca ratios in cores from all sites have a significant negative relationship with sea surface temperature (SST). The correlation coefficients (r) were -0.704, -0.651, -0.667 and -0.600 for Pulau Payar, Port Dickson, Pulau Tioman and Pulau Redang, respectively. Values from the 2010 El Niño event were plotted against the total Sr/Ca vs SST data and decline in the regression slope was observed in the Pulau Payar core. Sr/Ca calibration using the linear least squares equation showed that the intercept (A) and slope (B) values from Pulau Tioman and Port Dickson are very similar to Sr/Ca–SST relationships generated from high resolution coral series in other studies.